Adiponectin Interacts In-Vitro With Cementoblasts Influencing Cell Migration, Proliferation and Cementogenesis Partly Through the MAPK Signaling Pathway - Yong, Jiawen; von Bremen, Julia; Ruiz-Heiland, Gisela; Ruf, Sabine (Frontiers in Pharmacology, 2020)
Current clinical evidences suggest that circulating Adipokines such as Adiponectin can influence the ratio of orthodontic tooth movement. We aimed to investigate the effect that Adiponectin has on cementoblasts (OCCM-30) and on the intracellular signaling molecules of Mitogen-activated protein kinase (MAPK). We demonstrated that OCCM-30 cells express AdipoR1 and AdipoR2. Alizarin Red S staining revealed that Adiponectin increases mineralized nodule formation and quantitative AP activity in a dose-dependent manner. Adiponectin up-regulates the mRNA levels of AP, BSP, OCN as well as OPG. Adiponectin also increases the migration and proliferation of OCCM-30 cells. Moreover, Adiponectin induced a transient activation of JNK, P38, ERK1/2 and promotes the phosphorylation of STAT1 and STAT3. The activation of Adiponectin-mediated migration and proliferation was attenuated after pharmacological inhibition of P38, ERK1/2 and JNK in different degrees. Based on our results, Adiponectin may favorably affect OCCM-30 migration, proliferation as well as cementogenesis. The expression of AdipoRs suggests their involvement in obesity and orthodontic tooth movement. One of the underlying mechanisms is the activation of MAPK signaling pathways. Thus, Adiponectin may play a vital role on the progression of OCCM-30 cells, suggesting a potential novel role in the orthodontic treatment.